Student Stress Due to Online Learning During the Covid-19 Pandemic - Wahyu, Afnijar; Simanullang, Rostime Hermayerni (Universitas Aisyah Pringsewu, 2020)
Covid-19 is a disease caused by a viral infection that can spread very quickly and has spread to almost all countries, including Indonesia, in just a few months. In several countries, a policy has been made to lockdown in order to prevent the virus spreading and even in Indonesia a Large-Scale Social Restriction (PSBB) policy has been adopted to suppress the spread of this virus. As a result of the Lockdown, this has a major impact on changes in daily life from social life to education. The purpose of this study is to see a description of the students’ stress level due to online learning during Covid 19. The educational model that was once face-to-face has turned into an online system that stresses some students. Stress is a common phenomenon that occurs in modern life. Stress occurs generally because of the conflict that comes from high expectations and unreachable goals. The results of this study were conducted on 47 respondents, the research design was quantitative research using descriptive analysis. The results of this study showed as many as 48.9 percent of students experienced light stress, 42.6 percent and 4 percent experienced severe stress. The conclusion in this study is that students are in a light stress range (score 1-14) where students are able to adapt to changes in the learning process carried out through online. Abstrak: Covid-19 merupakan penyakit yang disebabkan oleh infeksi virus yang dapat menular dengan sangat cepat dan telah menyebar ke hampir semua negara, termasuk Indonesia, hanya dalam waktu beberapa bulan. Dibeberapa negara sudah membuat suatu kebijakan untuk melakukan lockdown dalam rangka mencegah penyebaran virus ini dan bahkan di Indonesia diambil suatu kebijakan Pembatasan Sosial Berskala Besar (PSBB) untuk menekan penyebaran virus ini. Akibat dari adanya Lockdown maka ini berdampak besar terhadap perubahan kehidupan sehari-hari mulai dali kehidupan sosial hingga pendidikan. Tujuan penelitian ini adalah melihat gambaran tingkat stress mahasiswa dalam pembelajaran daring selama Covid 19. Model pendidikan yang dulunya tatap muka berubah menjadi sistem Daring yang membuat sebagian mahasiswa stres. Stres merupakan fenomena umum yang terjadi dalam kehidupan modern. Stres terjadi umumnya karena konflik yang berasal dari harapan yang tinggi dan tujuan yang tidak terjcapai. Hasil penelitian ini dilakukan pada 47 responden, design penelitian adalah penelitian kuantitatif menggunakan analisis deskriptif. Hasil penelitian ini menunjukkan sebanyak 48,9 % mahasiswa mengalami stress ringan, sebanyak 42,6 % dan yang mengalami stress berat sebanyak 4 %. Simpulan dalam penelitian ini bahwa mahasiswa berada pada rentang stres ringan (skor 1-14) dimana mahasiswa mampu beradaptasi dengan perubahan proses pembelajaran yang dilakukan melalui Daring.